DEVELOPING TBLT-BASED DIGITAL STORYBOOK FOR 8TH-GRADE STUDENTS AT SMP NEGERI 4 SINGARAJA - Maharani, Ni Wayan Linda; Myartawan, I Putu Ngurah Wage; Pratiwi, Ni Putu Astiti (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2023)
This study aims to develop a digital storybook based on the TBLT method as a facility for literacy activities for grade 8 students at SMP Negeri 4 Singaraja. The method used in this research is the methodology of Richey and Klein (2014), namely the Design and Development research model. The data obtained in this study were collected with data collection instruments in the form of questionnaire interviews, observation, and document analysis. The quality of the digital storybook has been assessed by two experts with very good results and is tend to be valid to be used for learning media and encouraging literacy activities of grade 8 students.Â  This digital storybook has been trialed in small groups of grade 8 to get responses and conduct formative assessments. The results obtained from the trial of digital storybooks based on the TBLT method with "Recount Text" material for grade 8 can help teachers and students in creating innovative and communicative learning activities through the tasks contained in the storybook. This digital storybook product helps students in facilitate literacy activities.